Altered H3K27 trimethylation contributes to flowering time variations in polyploid Arabidopsis thaliana ecotypes. (26th October 2021) - Cheng, Jinping; Zhang, Guiqian; Xu, Linhao; Liu, Chang; Jiang, Hua
Abstract: Polyploidy is a widespread phenomenon in flowering plant species. Polyploid plants frequently exhibit considerable transcriptomic alterations after whole-genome duplication (WGD). It is known that the transcriptomic response to tetraploidization is ecotype-dependent in Arabidopsis; however, the biological significance and the underlying mechanisms are unknown. In this study, we found that 4 x Col-0 presents a delayed flowering time whereas 4 x L er does not. The expression of FLOWERING LOCUS C ( FLC ), the major repressor of flowering, was significantly increased in 4 x Col-0 but only a subtle change was present in 4 x L er . Moreover, the level of a repressive epigenetic mark, trimethylation of histone H3 at lysine 27 (H3K27me3), was significantly decreased in 4 x Col-0 but not in 4 x L er, potentially leading to the differences in FLC transcription levels and flowering times. Hundreds of other genes in addition to FLC showed H3K27me3 alterations in 4 x Col-0 and 4 x L er . LIKE HETEROCHROMATIN PROTEIN 1 (LHP1) and transcription factors required for H3K27me3 deposition presented transcriptional changes between the two ecotypes, potentially accounting for the different H3K27me3 alterations. We also found that the natural 4 x Arabidopsis ecotype Wa-1 presented an early flowering time, which was associated with low expression of FLC . Taken together, our results demonstrate a role of H3K27me3 alterations in response to genome duplication in Arabidopsis autopolyploids, and that variation in flowering time potentially functions in autopolyploid speciation. Abstract : Polyploidization in Arabidopsis alters trimethylation of histone H3 at lysine 27 in FLC and this is associated with variations in flowering time, which potentially functions in autopolyploid speciation.